2021
DOI: 10.3390/suschem2040031
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Förster Resonance Energy Transfer (FRET) in Ionic Materials

Abstract: Herein, an ionic material (IM) with Förster Resonance Energy Transfer (FRET) characteristics is reported for the first time. The IM is designed by pairing a Nile Blue A cation (NBA+) with an anionic near-infrared (NIR) dye, IR820−, using a facile ion exchange reaction. These two dyes absorb at different wavelength regions. In addition, NBA+ fluorescence emission spectrum overlaps with IR820− absorption spectrum, which is one requirement for the occurrence of the FRET phenomenon. Therefore, the photophysical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…FT-IR spectra were recorded on the Perkin Elmer Spectrum 100 FT-IR Spectrometer with ATR capability. 1 H-NMR, 13 C-NMR, 11 B-NMR, and 19 F-NMR spectra were recorded on Bruker Avance III 500 spectrometer in deuterated chloroform (CDCl 3 ). Electronic absorption spectra (UV-Vis) were recorded on Shimadzu UV-2450 UV-Visible Spectrophotometer.…”
Section: Materials and Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…FT-IR spectra were recorded on the Perkin Elmer Spectrum 100 FT-IR Spectrometer with ATR capability. 1 H-NMR, 13 C-NMR, 11 B-NMR, and 19 F-NMR spectra were recorded on Bruker Avance III 500 spectrometer in deuterated chloroform (CDCl 3 ). Electronic absorption spectra (UV-Vis) were recorded on Shimadzu UV-2450 UV-Visible Spectrophotometer.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Furthermore, according to classical FRET theory, the donor structure must have a high quantum yield (Φ) to enhance the process efficiency [7,8] . This critical mechanism, which is located between two interacting fluorophores, is used in a variety of advanced applications, including (bio)sensors, energy harvesting, and light‐emitting diodes [9–12] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by our research lab has shown the possibility of FRET mechanism in IMs/INMs upon removing spectator ions . Therefore, the FRET phenomenon in [Porph]­[IR783] IMs and INMs was investigated in three different solvents (ethanol, water, and PBS) and details of the spectra are provided in Figure S18.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by our research lab has shown the possibility of FRET mechanism in IMs/INMs upon removing spectator ions. 41 Therefore, the FRET phenomenon in [Porph][IR783] IMs and INMs was investigated in three different solvents (ethanol, water, and PBS) and details of the spectra are provided in Figure S18. The high spectral overlap integral (J(λ)) value (Table 2) obtained using eq S1 in the SI supports the possibility of energy transfer from porphyrin to IR783.…”
Section: Forster Resonance Energy Transfer (Fret)mentioning
confidence: 99%